Identification of Legionella, Indoor Air Quality and Employee Sick Building Syndrome Complaints in Installation of Blood Transfusion- Dr. Soetomo Hospital - Verayani, Erin (JURNAL KESEHATAN LINGKUNGAN, 2018)
Indoor air pollution was one of the factors causing global health problems because most people do activities in the room contaminated by pollutant materials. AC system was one of the factors that influence the air quality of the room. Improper maintenance to central air conditioning that was potentially as a breeding place for pathogenic microorganisms such as Legionella bacteria and decrease indoor air quality causing health problems of workers that is sick building syndrome. The purpose of this research was to know the existence of Legionella pathogen bacteria, indoor air quality such as physical and air bacteria number and sick building syndrome complaints on the officer at Blood Transfusion Installation of Dr.Soetomo Hospital. This study was an observational study with cross sectional study design and the results are compared with Minister of Health Decree No.1204 / Menkes / SK / X / 2004 about environmental health requirements of hospitals and Permenkes RI No.83 of 2014 about Blood Transfusion Unit. The results of identification in the water distribution system for clean water and AC Central using BCYE culture method was not found Legionella bacteria. The result of the measurement of the number of airborne germs has fulfilled the health requirements according to Minister of health Decree No.1204 / Menkes / SK / X / 2004 Environmental Health Requirements of hospital but the result of physical quality (temperature and humidity) was more than standart RI Minister of health Decree No.1204 / Menkes / SK / X / 2004 and Rule of Health Minister No.83/2014 about Blood Transfusion Unit. The result of this study showed that 84% staffs get sick building syndrome complaint. The most sick building syndrome complaints were dry eye (66,7%) and nasal congestion (61,9%).